Circular Depressed Cladding Waveguides in Mechanically Robust, Biocompatible nc-YSZ Transparent Ceramics by fs Laser Pulses - Guerra-Olvera, Cecilia; Castillo, Gabriel R.; Penilla, Elias H.; Uahengo, Gottlieb; Garay, Javier E.; Camacho-Lopez, Santiago (Journal of lightwave technology, 2019)
We report on the fabrication of depressed cladding waveguides inscribed by direct femtosecond laser pulses irradiation in transparent nc-yttria stabilized zirconia (YSZ) polycrystalline ceramics. The waveguides consisted of two different circular structures with diameters of 30 and 100 μm, and different lengths. Optical characterization at 633 and 1568 nm was performed. The obtained modal profiles show dependence on the structure and size of the waveguides. We estimate a laser-induced refractive index contrast of nearly 10 -2 , larger than can be explained by induced residual stresses alone. We conjecture that laser interactions lead to localized physical damage, i.e., microvoids cracks and possibly a decreased degree of crystallinity in the laser processed zones, which is supported by Raman measurements. Our results suggest a promising potential use of nc-YSZ in photonic bio-applications.